(untitled) (PJDOL, 2023)
, Distance learning is one of the fastest growing areas of education in recent years. Despite the recent significant developments in the electronic networking world, particularly the recent global focus on the Internet, which provides major technical thrusts, other emerging technologies have also committed to changing the pattern of general education, with particularly intensifying distance education.